Household Sanitation Practices Escalating Diarrhea in Children Under-Five in Igembe South Sub County, Meru County, Kenya. - Anampiu, jacob (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Aim: The study aimed to identify household sanitation risk factors contributing to diarrhea in children under-five years in Igembe South Sub County, Meru County, Kenya. Methodology: This retrospective study was conducted at Nyambene Sub County Hospital in Maua Town and used convenience sampling to choose 196 children under the age of five who were treated for diarrhea between December 2022 and March 2023. These cases were followed up at home to gather information on household sanitation, water, and hygiene practices using questionnaires and observations. Water samples from domestic sources were tested at Meru University of Science and Technology. Data was analyzed using SPSS version 24, with ANOVA used to investigate hygiene and sanitation variables. Results: The study received a 100% response rate, with 63.3% of caregivers being women and 46.4% being mothers. The degree of education varied, with 55.1% having completed secondary school. Immunization Status: 75.5% of children were partially immunized, with only 24.5% being fully immunized against rotavirus. Latrines were available in 70.4% of households, with 57.7% of them being improved. However 45.4% of caretakers used diapers, whereas 43.9% disposed of their excrement in pit latrines. Only 68.9% cleaned their hands after touching child feces. 57% had hand washing facilities, whereas 51% had soap available. Education on hand hygiene was received by 81% of participants. Discussion: Regression analysis revealed significant hygiene and sanitation factors influencing diarrhea prevalence, including hand washing before preparing meals (p=0.048) and household water supply (p=0.042). Poorly used and maintained sanitation facilities, as well as contaminated water sources, were major causes. Conclusion: The study emphasizes the importance of improving sanitation, water safety, and hygiene practices in reducing diarrhea among children under five in Igembe South.